Coal gangue-based aqueous zinc-ion battery negative electrode protective coating and preparation method and application thereof

CN123017964APending Publication Date: 2026-10-30INNER MONGOLIA UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410557317.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但普遍存在电化学性能差、浸润性不足、孔隙率小的特点且涂层在锌离子电池中仅起到物理阻挡溶剂水与锌阳极直接接触的作用

Benefits of technology

[0058](1)本发明采用的磨矿工艺可以降低煤矸石的粒度,提高物料的反应性,避免因颗粒较大,导致煤矸石颗粒内外受热不均,避免在煅烧过程中煤矸石反应不完全。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017964A_ABST
    Figure CN123017964A_ABST
Patent Text Reader

Abstract

The application discloses a coal gangue-based aqueous zinc ion battery negative electrode protective coating and a preparation method and application thereof, and belongs to the technical field of battery materials.The amorphous metakaolin obtained by calcining coal gangue is mixed with a binder and then stirred to prepare a slurry, and finally the slurry is uniformly coated on the surface of a zinc foil by a doctor blade method, and a metakaolin coating is formed on the surface of the zinc foil after drying, namely the zinc ion battery negative electrode protective coating.The protective coating prepared by the application is mainly composed of metakaolin.After being ground and calcined, the kaolin in the coal gangue is converted into high-activity amorphous metakaolin.The metakaolin has small particle size and large specific surface area, can form a reticular structure with large porosity, and has increased contents of silicon dioxide and aluminum trioxide and increased active points, so that the zinc ions can be effectively and uniformly transmitted, and the performance of the zinc ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery materials technology, specifically relating to a protective coating for the negative electrode of an aqueous zinc-ion battery based on coal gangue, its preparation method, and its application. Background Technology

[0002] Zinc is abundant, inexpensive, chemically stable, and safe, and has a high theoretical specific capacity (820 mAh g). -1 With its low oxidation-reduction potential (-0.76V vs. SHE), it is environmentally friendly and the best anode choice for aqueous zinc-ion batteries.

[0003] However, the zinc dendrite growth, hydrogen evolution, and zinc corrosion present in the zinc anode severely affect the reversibility and cycle performance of zinc-ion batteries. Currently, the main optimization strategies for these problems focus on zinc anode design, electrolyte optimization, the introduction of electrolyte additives, and separator optimization. Among these, artificial zinc anode coatings are highly adaptable and easy to operate, effectively controlling local ion concentration and flux while significantly suppressing zinc dendrite growth and hydrogen evolution. Zhang et al. coated commercially available zinc foil with a specifically oriented TiO2 protective layer, enabling a zinc-ion symmetric battery to achieve a cycle performance of 1 mA cm⁻¹. -2 Stable cycling for 460 h under suitable conditions. Chen et al. prepared a polyacrylonitrile coating on the zinc anode using a drop-coating method. The coating effectively improved the hydrophilicity of the zinc anode, regulated the transport of zinc ions, and prevented dendrite formation. Zhao et al. constructed a polyamide coating with a unique hydrogen bond network and strong coordination with metal ions, effectively controlling the deposition behavior of zinc in the aqueous phase. The zinc anode could operate stably for more than 8000 h without dendrite formation, and the assembled full cell had 88% capacity retention after 100 cycles. Dong et al. constructed a dense and robust -NH2 functionalized polysilane layer on zinc foil. -NH2 and Zn 2+ The strong interaction makes Zn 2+ Uniform deposition of Si-O-Zn allows for a durable interlayer bond between the zinc foil and the polysilane, resulting in excellent electrochemical performance. Li et al. prepared a zinc-loving, hydrophobic copper-modified Ti3C2Cl2 MXene material for use as a zinc anodic protective coating, achieving good electrochemical performance at 10 mA cm⁻¹. -2 The polarization potential is less than 120mV at current density, and the coulombic efficiency remains above 99.6% after 1100 cycles.

[0004] Although new methods, materials, and improvements have been proposed for zinc anode protective coatings in recent years, they generally suffer from poor electrochemical performance, insufficient wettability, and low porosity. Furthermore, in zinc-ion batteries, these coatings primarily serve to physically prevent direct contact between the solvent water and the zinc anode. Therefore, developing a simple, low-cost, and widely applicable strategy to address dendrite growth and side reactions in aqueous zinc-ion batteries is a key focus of research. Consequently, designing and fabricating low-cost coatings with high-quality dynamic interfaces to protect zinc anodes is urgently needed. Summary of the Invention

[0005] Based on the above reasons, the technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a protective coating for the negative electrode of an aqueous zinc-ion battery based on coal gangue, its preparation method and application, to solve or at least partially solve the above-mentioned technical defects in the prior art: the present invention aims to solve the problems of dendrite growth, corrosion and side reactions occurring at the zinc anode in aqueous zinc-ion batteries, and improve the electrochemical performance of zinc-ion batteries, providing a new way for the high-value utilization of bulk solid waste coal gangue.

[0006] To achieve one of the above-mentioned objectives of the present invention, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a protective coating for the negative electrode of an aqueous zinc-ion battery based on coal gangue, the method specifically includes the following steps:

[0008] 1) Grind the coal gangue raw material and sieve it to obtain finely ground coal gangue;

[0009] 2) The finely ground coal gangue described in step 1) is calcined to obtain amorphous metakaolin.

[0010] 3) Grind the amorphous metakaolin described in step 2), then mix it with the binder according to the ratio and dry it. Then disperse the dried mixture in an organic solvent, mix it evenly, and obtain a uniform slurry.

[0011] 4) The slurry described in step 3) is coated onto the pretreated zinc foil surface and dried to obtain the aqueous zinc-ion battery negative electrode protective coating based on coal gangue.

[0012] Furthermore, in the above technical solution, step (1), in a preferred embodiment of the present invention, the grinding equipment used is a GT-2 sealed sample preparation pulverizer. In this invention, the coal gangue is first ground using a GT-2 sealed sample preparation pulverizer. The ground coal gangue has a uniform particle size distribution, providing a material basis for subsequent complete calcination.

[0013] Specifically, in the above technical solution, the reason why the GT-2 sealed sample preparation pulverizer is preferred to grind the coal gangue raw material in step (1) is as follows: The present invention controls the particle size of the coal gangue. By comparing the particle size of the products ground by the GT-2 sealed sample preparation pulverizer and the RK / GQM-φ305X305 grinding power index ball mill (see this application), Figure 1 It was found that compared to other grinding equipment, the GT-2 sealed sample preparation and pulverizing mill produces products with advantages such as uniform particle size distribution and low energy consumption. This is because the GT-2 sealed sample preparation and pulverizing mill eliminates the need for sieving, allowing for direct use of the sample, reducing processing steps, increasing production efficiency, and its sealed pulverizing chamber design prevents coal gangue powder from escaping. In contrast, the product obtained using the RK / GQM-φ305X305 grinding power index ball mill exhibits uneven particle size distribution and larger particle sizes. Therefore, this invention ultimately determined to use the GT-2 sealed sample preparation and pulverizing mill for grinding coal gangue.

[0014] Furthermore, in the above technical solution, in step (1), the grinding medium used is any one of steel balls, steel rods, gravel, etc. In a preferred embodiment of the present invention, the grinding medium used is steel balls.

[0015] Furthermore, in the above technical solution, in step (1), the ball-to-material ratio is 200-350:1. In a preferred embodiment of the present invention, the ball-to-material ratio is 300. Here, the ball-to-material ratio is the mass ratio between the grinding media and the material inside the ball mill.

[0016] Furthermore, in the above technical solution, in step (1), the grinding time is 1-10 min, and in a preferred embodiment of the present invention, the grinding time is 6 min.

[0017] Furthermore, in the above technical solution, in step (1), the particle size of the ground coal gangue is 20-100 μm. In a preferred embodiment of the present invention, the particle size of the ground coal gangue is less than 75 μm.

[0018] Furthermore, in a preferred embodiment of the present invention, step 2) of the above technical solution involves calcining finely ground coal gangue in a tubular furnace, after which the coal gangue forms amorphous metakaolin (…). Figure 2 In the calcination process of this invention, as the calcination temperature increases, the Al-OH bonds of kaolin in the coal gangue break and hydroxyl groups are released, thus destroying the layered structure of the kaolin. Figure 2 The diffraction peaks at 12.4°, 24.9° and 37.8° completely disappeared, and a diffuse dome-shaped peak appeared at 20-25°, indicating that the kaolinite was completely transformed into an amorphous phase mineral, that is, calcined into amorphous metakaolinite.

[0019] Furthermore, in step 2) of the above technical solution, the calcination process uses a mixed gas, preferably a mixture of N2 and O2. In a preferred embodiment of the present invention, the volume ratio of N2 to O2 is 4:1.

[0020] Furthermore, in the above technical solution, the total gas flow rate of the mixed gas is 200-700 mL / min. In a preferred embodiment of the present invention, the total gas flow rate of the mixed gas is 500 mL / min.

[0021] Furthermore, in step 2) of the above technical solution, the calcination temperature is 500-1000℃. In a preferred embodiment of the present invention, the calcination temperature is 800℃.

[0022] Furthermore, in the above technical solution, step 2), the calcination time is 2-5 hours. In a preferred embodiment of the present invention, the calcination time is 4 hours.

[0023] Furthermore, in the above technical solution, step 2), the heating rate to the calcination temperature is 5-20℃ / min. In a preferred embodiment of the present invention, the heating rate is 10℃ / min.

[0024] Specifically, in step 3) of the above technical solution, the amorphous metakaolin is ground in order to uniformly refine some of the amorphous metakaolin and make the particle size of the amorphous metakaolin less than 75μm.

[0025] Furthermore, in step 3) of the above technical solution, the adhesive is either polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE). In a preferred embodiment of the present invention, the adhesive is polyvinylidene fluoride (PVDF).

[0026] Furthermore, in the above technical solution, step 3), in a preferred embodiment of the present invention, the organic solvent is N-methylpyrrolidone (NMP).

[0027] Further, in step 3) of the above technical solution, the mass ratio of the amorphous metakaolin to the binder is 9:1-9:4, more preferably 9:1-9:3. In a preferred embodiment of the present invention, the mass ratio of the amorphous metakaolin to the binder is 9:1.

[0028] Furthermore, in the above technical solution, step 3), the purpose of drying the mixture of amorphous metakaolin and binder is to remove moisture from the mixture and prevent excessive moisture from affecting the solubility of the binder in the organic solvent. In a preferred embodiment of the present invention, the drying temperature is 90°C and the drying time is 8 hours.

[0029] Further, in step 3) of the above technical solution, the mass ratio of the amorphous metakaolin to the organic solvent is 1-4:1. In a preferred embodiment of the present invention, the mass ratio of the amorphous metakaolin to the organic solvent is 3:1.

[0030] Furthermore, in step 4) of the above technical solution, the pretreatment method of the zinc foil specifically involves grinding the zinc foil to remove the oxide layer, then cleaning it with anhydrous ethanol and drying it. The purpose is to completely remove the ethanol and avoid the coating failing to adhere to the zinc foil due to the presence of ethanol.

[0031] Furthermore, in step 4) of the above technical solution, the coating method includes blade coating, drop coating, roller coating, curtain coating, spin coating, etc. In a preferred embodiment of the present invention, the coating method is blade coating.

[0032] Furthermore, in the above technical solution, in step 4), the thickness of the protective coating after coating and drying is 5-25 μm. In a preferred embodiment of the present invention, the thickness of the protective coating after coating and drying is 10 μm.

[0033] Furthermore, in step 4) of the above technical solution, the drying temperature is 80-120℃, more preferably 90-110℃. In a preferred embodiment of the present invention, the drying temperature is 90℃.

[0034] Furthermore, in the above technical solution, in step 4), the drying process uses a baking time of 10-15 hours. In a preferred embodiment of the present invention, the drying process uses a baking time of 12 hours.

[0035] A second objective of this invention is to provide a protective coating for the negative electrode of an aqueous zinc-ion battery based on coal gangue, prepared using the method described above.

[0036] A third objective of this invention is to provide the application of the protective coating prepared by the method described above in the negative electrode of an aqueous zinc-ion battery.

[0037] The fourth objective of this invention is to provide an aqueous zinc-ion battery anode, comprising a protective coating for the aqueous zinc-ion battery anode based on coal gangue prepared by the method described above.

[0038] The fifth objective of this invention is to provide an aqueous zinc-ion battery, comprising a positive electrode, a negative electrode, a separator between the positive and negative electrodes, and an electrolyte, wherein the negative electrode is the negative electrode of the aqueous zinc-ion battery described above.

[0039] A sixth objective of this invention is to provide a method for detecting the electrochemical performance of the protective coating for the negative electrode of an aqueous zinc-ion battery based on coal gangue prepared by the above-described preparation method, wherein the method includes the following steps:

[0040] 1) Preparation of Zn / MnO2 full cells using MnO2 as the positive electrode material of rechargeable zinc-ion batteries: MnO2 powder, conductive carbon black and binder were weighed in sequence according to the formula, mixed and then an organic solvent was added to disperse evenly to obtain a uniform slurry.

[0041] 2) The slurry described in 1) is slowly and evenly coated onto a smooth stainless steel foil surface using a coating machine, and then heated and dried to be used as the positive electrode sheet for zinc-ion batteries.

[0042] 3) Cut stainless steel foil with MnO2 positive electrode material and zinc foil negative electrode with metakaolin protective coating into disc-shaped electrodes;

[0043] 4) A button-type zinc-ion battery is assembled using stainless steel foil with MnO2 as the positive electrode, zinc foil with metakaolin protective coating as the negative electrode, and glass fiber membrane as the separator. The electrolyte is an aqueous solution of ZnSO4 and MnSO4.

[0044] 5) A Zn / Zn symmetrical cell was assembled using zinc foil with a metakaolin negative electrode protective coating as the electrode and a glass fiber membrane as the separator, with an aqueous ZnSO4 solution as the electrolyte.

[0045] 6) Test the battery performance on the assembled battery workstation and electrochemical testing system.

[0046] Furthermore, in the above technical solution, in step 1), the mass ratio of the MnO2 powder, conductive carbon black, and PVDF binder is 7:2:1.

[0047] Furthermore, in the above technical solution, in step 1), the binder is preferably PVDF, and the organic solvent is preferably NMP.

[0048] Furthermore, in step 3) of the above technical solution, the diameters of the disc-shaped electrodes are 1.3 cm and 1.5 cm, respectively, and the effective loading of MnO2 on the positive electrode is 6 mg / cm³. 2 .

[0049] Furthermore, in the above technical solution, in step 4), the diameter of the glass fiber diaphragm is 2 cm.

[0050] Furthermore, in the above technical solution, in step 4), the electrolyte is an aqueous solution of 2M ZnSO4 and 0.1M MnSO4.

[0051] Furthermore, in the above technical solution, in step 5), the diameter of the electrode with the metakaolin negative electrode protective coating is 1.3 cm; the diameter of the glass fiber diaphragm is 2 cm.

[0052] Furthermore, in the above technical solution, in step 5), the concentration of the ZnSO4 aqueous solution is 2M.

[0053] The mechanism involved in this invention is as follows:

[0054] The protective coating obtained by this invention is mainly composed of metakaolin. After calcination, the kaolin in the finely ground coal gangue is transformed into highly active amorphous metakaolin. The metakaolin has a small particle size and a large specific surface area, forming a network structure with high porosity. The content of silica and alumina increases, and the number of active sites increases, enabling effective and uniform transport of zinc ions, thereby improving the performance of zinc-ion batteries.

[0055] This invention involves mixing amorphous metakaolin obtained from calcined coal gangue with a binder to form a slurry. The slurry is then preferably coated evenly onto a zinc foil surface using a scraping method. After drying, a metakaolin coating is formed on the zinc foil surface, which is the aforementioned protective coating for the negative electrode of a zinc-ion battery. This coating exhibits excellent corrosion resistance and effectively inhibits zinc dendrite growth. It acts as a physical barrier and ion transport mechanism, effectively regulating zinc ion migration while preventing short circuits caused by zinc dendrites contacting the positive electrode and suppressing the formation of byproducts.

[0056] This invention takes into account the comprehensive utilization of bulk solid waste and the practical application of zinc-ion batteries. The main challenge is how to change the previous extensive utilization of coal gangue to refined and high-value utilization, and promote the innovative development of comprehensive utilization of coal gangue.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] (1) The grinding process used in this invention can reduce the particle size of coal gangue, improve the reactivity of the material, avoid uneven heating inside and outside the coal gangue particles due to large particle size, and avoid incomplete reaction of coal gangue during calcination.

[0059] (2) From the perspective of raw materials, coal gangue is one of the largest industrial solid wastes emitted during coal mining and washing in my country. This invention selects coal gangue, a cheap and readily available bulk solid waste, to prepare an anode protective coating for aqueous zinc-ion batteries, which can improve the high-value utilization level of coal gangue, improve environmental quality, and promote the comprehensive green transformation of economic and social development.

[0060] (3) In terms of calcination process, this invention adopts suspension roasting process for coal gangue calcination. Compared with the traditional muffle furnace calcination process, the suspension roasting process has the advantages of being safe and reliable, simple to operate, high temperature control accuracy, controllable gas, good heat preservation effect, large temperature range, high furnace temperature uniformity, complete calcination, and multiple temperature zones.

[0061] (4) In terms of coating preparation method, the present invention preferably uses the scraping method to coat metakaolin obtained by calcining coal gangue onto the zinc anode surface. The advantage is that it can quickly form a uniform film on a large surface area, which is suitable for industrial production of zinc anode surface coating.

[0062] (5) Compared with the prior art, the present invention is easy to operate and can prepare an environmentally friendly, non-toxic and harmless calcined kaolin negative electrode protective coating without the need for expensive and precision instruments. The resulting coating has excellent corrosion resistance, acts as a physical barrier and ion transport, can effectively regulate the migration of zinc ions, and at the same time avoids short circuits in the battery caused by zinc dendrites contacting the positive electrode, and inhibits the formation of by-products.

[0063] (6) The method for preparing the protective coating in this invention is simple, suitable for large-scale preparation, and quick. The zinc-ion battery prepared with the calcined coal gangue negative electrode protective coating is green, environmentally friendly, low-cost, and non-toxic. The entire preparation process of the coating and zinc-ion battery can be completed at room temperature and in air, without the need for specialized instruments such as glove boxes, making it highly efficient and fast. The battery with the calcined coal gangue negative electrode protective coating prepared by this invention can undergo various tests and exhibits excellent electrochemical performance, demonstrating the effectiveness and reliability of the method. Attached Figure Description

[0064] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0065] Figure 1 (a) and (b) are comparison diagrams of particle size classification of the grinding products obtained by the GT-2 sealed sample preparation pulverizer used in this invention and the RK / GQM-φ305X305 grinding power index ball mill used in the comparative example.

[0066] Figure 2 The XRD pattern of amorphous metakaolinite prepared in Example 1 of this invention;

[0067] Figure 3(a) is a SEM image of the zinc anode of Comparative Example 1 after 300 cycles. Figure 3 (b) is a SEM image of the zinc foil exposed after the coating on the zinc anode of Comparative Example 1 was peeled off after 300 cycles.

[0068] Figure 4 This is a schematic diagram of the preparation method and electrochemical testing process for the negative electrode protective coating of an aqueous zinc-ion battery based on coal gangue according to the present invention.

[0069] Figure 5 To compare the bare zinc and the Zn / Zn symmetric cell with metakaolin anode protective coating in Example 1 at 0.4 mA / cm 2 Comparison of time-voltage curves after 1000 hours of cycling at current density;

[0070] Figure 6 This is a comparison chart of the long-cycle performance of bare zinc and full cells with metakaolinite anode protective coating in Comparative Example 1 under 3C operation.

[0071] Figure 7 The diagram shows the significant volume expansion of the full cell with the uncalcined kaolin negative electrode protective coating in Comparative Example 2 during operation.

[0072] Figure 8 The image shows the SEM image of the zinc anode with a protective coating of calcined kaolin clay after calcination at 400℃ in Comparative Example 3 after long cycling, after which the coating is peeled off to expose the bare zinc foil.

[0073] Figure 9 A comparison chart of the rate performance of bare zinc and the full cell with metakaolin anode protective coating in Comparative Example 3.

[0074] Figure 10 The image shows the SEM image of the zinc anode with a protective coating of calcined kaolin clay after calcination at 1100℃ in Comparative Example 4 after long cycling, after which the coating is peeled off to expose the bare zinc foil.

[0075] Figure 11 To compare the bare zinc and the Zn / Zn symmetric cell with metakaolin anode protective coating in Example 4 at 0.5 mA / cm 2 Comparison of time-voltage curves under current density cycling;

[0076] Figure 12 The image shows the contact angle test results of the calcined coal gangue coating after calcination at different temperatures of 500℃, 600℃, 700℃, 800℃, 900℃, and 1100℃ in Comparative Example 5.

[0077] Figure 13In Comparative Example 5, (a)-(f) are comparative images of the surface morphology of the zinc anode after calcination of coal gangue coating at 500℃, 600℃, 700℃, 800℃, 900℃ and 1100℃ respectively, after 300 cycles.

[0078] Figure 14 The bare zinc and Zn / Zn symmetric cell with metakaolin anode protective coating in Example 2 were tested at 0.2 mA / cm². 2 Time-voltage curves after 800 hours of cycling at current density;

[0079] Figure 15 The bare zinc and Zn / Zn symmetric cell with metakaolin anode protective coating in Example 3 were tested at 4.4 mA / cm². 2 Cycle time-voltage curve at current density;

[0080] Figure 16 For the bare zinc and Zn / Zn symmetric cell with metakaolin anode protective coating in Example 4, the 1 mA / cm 2 Time-voltage curves after 900 hours of cycling at current density;

[0081] Figure 17 For the bare zinc and Zn / Zn symmetric cell with metakaolin anode protective coating in Example 5, the current is 1.8 mA / cm. 2 Time-voltage curves after 50 hours of cycling at current density;

[0082] Figure 18 Comparison of long-cycle performance of bare zinc and full cells with metakaolin anode protective coating in Example 6 under 5C operation. Detailed Implementation

[0083] The present invention will be further described in detail below through implementation examples. These implementation examples are carried out based on the technology of the present invention. Detailed implementation methods and specific operating procedures are provided to illustrate the inventiveness of the present invention, but the scope of protection of the present invention is not limited to the following implementation examples.

[0084] The equipment and raw materials used in this invention are all commercially available or commonly used in the field. Unless otherwise specified, the methods in the following embodiments are conventional methods in the field.

[0085] The coal gangue used in the following embodiments or comparative examples of the present invention is high-alumina coal gangue from the Jungar region of Inner Mongolia, specifically recovered from the Suancigou Coal Mine of Inner Mongolia Yitai Jingyue Suancigou Mining Co., Ltd., and its main chemical composition is shown in Table 1.

[0086] Table 1

[0087]

[0088] The GT-2 sealed sample preparation pulverizer used in the following embodiments of the present invention is a GT-2 model, purchased from Jiangxi Yinrui Mining and Metallurgical Equipment Co., Ltd., and the weight of the whole machine is 105KG.

[0089] The RK / GQM-φ305X305 grinding power index ball mill used in Comparative Example 5 of the present invention was purchased from Wuhan Locke Grinding Equipment Manufacturing Co., Ltd., and the product model is RK / GQM.

[0090] Example 1

[0091] This embodiment discloses a method for preparing a protective coating for the negative electrode of an aqueous zinc-ion battery based on coal gangue. The method specifically includes the following steps:

[0092] (1) Take 50g of coal gangue with a particle size of 3-5cm and place it in a GT-2 sealed sample preparation pulverizer. Grind for 6 minutes using steel balls as the grinding media. The specific amounts of steel balls used are: 4.4kg of 30mm steel balls, 5.74kg of 25mm steel balls, 3.04kg of 20mm steel balls, and 1.82kg of 15mm steel balls. After grinding, pass the coal gangue through a 200-mesh sieve to obtain finely ground coal gangue with a particle size of less than 75μm, which is then ready for use.

[0093] (2) Take 1g of the finely ground coal gangue described in (1) and place it in a VTL1500 vertical tube furnace for calcination. The simulated gas is formed by mixing two gases (N2 and O2) in a mixing box (VN2∶VO2=4∶1). The total gas flow rate is 500mL / min, the heating rate is 10℃ / min, the calcination temperature is 800℃, and the calcination time is 4h to obtain amorphous metakaolin.

[0094] (3) The amorphous metakaolin described in (2) is placed in a mortar and ground until the particle size is less than 75 μm. Take 0.9 g of the ground amorphous metakaolin and 0.1 g of polyvinylidene fluoride (PVDF), mix them, and bake them in a forced-air drying oven at 90°C for 8 h.

[0095] (4) Disperse the mixture obtained from drying in (3) in 4.5 ml of N-methylpyrrolidone (NMP) and stir thoroughly for 12 h to obtain a uniform slurry.

[0096] (5) Polish the zinc foil to remove the oxide layer, and then clean it with anhydrous ethanol. After the ethanol has completely evaporated, the pretreated zinc foil is obtained. Then place the pretreated zinc foil on a coating machine and coat it with the slurry mentioned in (4). The coating thickness is 10 μm.

[0097] (6) The zinc foil with coating obtained in (5) is placed in a muffle furnace and baked at 90°C for 12 hours to obtain the aqueous zinc-ion battery negative electrode protective coating based on coal gangue, that is, the zinc foil with metakaolin negative electrode protective coating.

[0098] control group

[0099] The RK / GQM-φ305X305 grinding power index ball mill was used to grind coal gangue. The specific operating steps are as follows:

[0100] Take 50g of coal gangue with a particle size of 3-5cm and place it in an RK / GQM-φ305X305 grinding power index ball mill. Grind for 6 minutes using steel balls as the grinding media. The specific amounts of steel balls used are: 4.4kg of 30mm steel balls, 5.74kg of 25mm steel balls, 3.04kg of 20mm steel balls, and 1.82kg of 15mm steel balls. After grinding, pass the coal gangue through a 200-mesh sieve to obtain finely ground coal gangue with a particle size of less than 75μm, which is then ready for use.

[0101] Figure 1 In the middle (a) and (b), respectively, the particle size classification of the powder products obtained by the GT-2 sealed sample preparation pulverizer used in Example 1 of the present invention and the RK / GQM-φ305X305 grinding power index ball mill used in the control group are compared. Figure 1 The specific test methods corresponding to (a) and (b) are as follows: the finely ground coal gangue is dispersed in deionized water without pH adjustment, the solution is sonicated for 5 minutes and then directly dripped into the sample cell. The sample cell is placed in a nanoparticle size and Zeta potential analyzer (ZetasizerNano ZS) for particle size distribution testing.

[0102] It can be seen that, compared with other grinding equipment, the peak values ​​of the particle size distribution curves of the products obtained from the GT-2 sealed sample preparation and pulverizing mill are relatively concentrated, close to a normal distribution, indicating good particle size consistency and uniform particle size distribution. This is because the GT-2 sealed sample preparation and pulverizing mill samples do not require sieving and can be used directly, with fewer steps, high production efficiency, and a sealed pulverizing chamber design that prevents coal gangue powder from escaping. In contrast, the products obtained using the RK / GQM-φ305X305 grinding power index ball mill have uneven particle size distribution and larger particle sizes. Therefore, this invention ultimately determines to use the GT-2 sealed sample preparation and pulverizing mill for grinding coal gangue.

[0103] In Example 1 of this invention, coal gangue was first ground using a GT-2 sealed sample preparation pulverizer. The ground coal gangue had a uniform particle size distribution, providing a material basis for subsequent complete calcination. The coal gangue was then placed in a vertical tubular furnace for calcination. After calcination, the coal gangue formed amorphous metakaolinite. The increased calcination temperature caused the Al-OH bonds in the coal gangue to break and hydroxyl groups to be released, destroying the layered structure of the coal gangue. The diffraction peaks at 12.4°, 24.9°, and 37.8° completely disappeared, and a diffuse dome-shaped peak appeared at 20-25°, forming an amorphous phase mineral containing a large amount of alumina, indicating that it was calcined into metakaolinite.

[0104] The electrochemical performance of the aqueous zinc-ion battery anode protective coating based on coal gangue prepared in Example 1 was tested:

[0105] (1) Weigh 0.7g of MnO2 powder, 0.2g of conductive carbon black and 0.1g of PVDF. Mix them evenly in a 20mL glass bottle, add 4.5mL of NMP as solvent, and stir magnetically for 8h to obtain a uniform slurry.

[0106] (2) The slurry is slowly and evenly coated onto the smooth stainless steel foil surface using a coating machine, and then it is heated and baked at 90°C for 12 hours in a forced-air drying oven to completely remove the solvent, and used as the positive electrode sheet for zinc-ion batteries.

[0107] (3) Stainless steel foil with MnO2 positive electrode material and negative electrode with metakaolin protective coating were cut into disc-shaped electrodes with diameters of 1.3 cm and 1.5 cm, respectively. The effective loading of MnO2 on the positive electrode was 6 mg / cm³. 2 .

[0108] (4) A button-type zinc-ion battery was assembled using stainless steel foil with MnO2 as the positive electrode, zinc foil with metakaolin negative electrode protective coating prepared in Example 1 as the negative electrode, and glass fiber membrane with a diameter of 2 cm as the separator. The electrolyte was an aqueous solution of 2M ZnSO4 and 0.1M MnSO4.

[0109] (5) A Zn / Zn symmetrical cell was assembled using zinc foil with a metakaolin negative electrode protective coating prepared in Example 1 with a diameter of 1.3 cm as the electrode and glass fiber membrane with a diameter of 2 cm as the separator. The electrolyte was a 2M aqueous solution of ZnSO4.

[0110] (6) Use the Blue Battery Testing System to test the electrochemical performance.

[0111] A schematic diagram of the preparation method and electrochemical testing process for the negative electrode protective coating of an aqueous zinc-ion battery based on coal gangue is shown below. Figure 4 .

[0112] Example 2

[0113] This embodiment discloses a method for preparing a protective coating for the negative electrode of an aqueous zinc-ion battery based on coal gangue. The method specifically includes the following steps:

[0114] (1) Take 50g of coal gangue with a particle size of 3-5cm and place it in a GT-2 sealed sample preparation pulverizer. Grind for 4 minutes using steel balls as the grinding media. The specific amounts of steel balls used are: 4.4kg of 30mm steel balls, 5.74kg of 25mm steel balls, 3.04kg of 20mm steel balls, and 1.82kg of 15mm steel balls. After grinding, pass the coal gangue through a 200-mesh sieve to obtain finely ground coal gangue with a particle size of less than 75μm, which is then ready for use.

[0115] (2) Take 1g of finely ground coal gangue from (1) and place it in a VTL1500 vertical tube furnace for calcination. The simulated gas is formed by mixing two gases (N2 and O2) in a mixing box (VN2∶VO2=4∶1). The total gas flow rate is 300mL / min, the heating rate is 10℃ / min, the calcination temperature is 700℃, and the calcination time is 3h to obtain amorphous metakaolin.

[0116] (3) The amorphous metakaolin stone is placed in a mortar and ground until the particle size is less than 75μm. Take 0.7g of the ground amorphous metakaolin and 0.3g of PVDF, mix them, and bake them in a forced-air drying oven at 90℃ for 8h.

[0117] (4) Disperse the mixture obtained from drying in (3) in 3.5 ml of NMP and stir thoroughly for 12 h to obtain a uniform slurry.

[0118] (5) The zinc foil is polished to remove the oxide layer, and then cleaned with anhydrous ethanol. After the ethanol has completely evaporated, the pretreated zinc foil is obtained. Then the pretreated zinc foil is placed on a coating machine, and the slurry in (4) is placed on the zinc foil for coating. The coating thickness is 13μm.

[0119] (6) The zinc foil with coating obtained in (5) is placed in a muffle furnace and baked at 100°C for 12 hours to obtain the aqueous zinc-ion battery negative electrode protective coating based on coal gangue, i.e., the zinc foil with metakaolin negative electrode protective coating.

[0120] The electrochemical performance of the aqueous zinc-ion battery anode protective coating based on coal gangue prepared in this embodiment was tested:

[0121] (1) A Zn / Zn symmetrical cell was assembled using zinc foil with a metakaolin negative electrode protective coating prepared in Example 2 with a diameter of 1.3 cm as the electrode and glass fiber membrane with a diameter of 2 cm as the separator. The electrolyte was a 2M aqueous solution of ZnSO4.

[0122] (2) Use the Blue Battery Testing System to test the electrochemical performance.

[0123] Figure 14 The results of Example 2 show a Zn / Zn symmetric cell with bare zinc and a metakaolin anode protective coating at 0.2 mA / cm². 2 The time-voltage curves under 800h cycling at current density show that the overpotential of the coated symmetrical cell (average 42mV) is lower than that of the bare zinc electrode (average 78mV), indicating that the metakaolin anode protective coating does indeed reduce the overpotential of zinc ion deposition and accelerates the zinc ion deposition / stripping process.

[0124] Example 3

[0125] This embodiment discloses a method for preparing a protective coating for the negative electrode of an aqueous zinc-ion battery based on coal gangue. The method specifically includes the following steps:

[0126] (1) Take 50g of coal gangue with a particle size of 3-5cm and place it in a GT-2 sealed sample preparation pulverizer. Grind for 5 minutes using steel balls as the grinding media. The specific amounts of steel balls used are: 4.4kg of 30mm steel balls, 5.74kg of 25mm steel balls, 3.04kg of 20mm steel balls, and 1.82kg of 15mm steel balls. After grinding, pass the coal gangue through a 200-mesh sieve to obtain finely ground coal gangue with a particle size of less than 75μm, which is then ready for use.

[0127] (2) Take 1g of finely ground coal gangue from (1) and place it in a VTL1500 vertical tube furnace for calcination. The simulated gas is formed by mixing two gases (N2 and O2) in a mixing box (VN2∶VO2=4∶1). The total gas flow rate is 400mL / min, the heating rate is 10℃ / min, the calcination temperature is 600℃, and the calcination time is 3h to obtain amorphous metakaolin.

[0128] (3) The amorphous metakaolin described in (2) is placed in a mortar and ground until the particle size is less than 75μm. Take 0.8g of the ground amorphous metakaolin and 0.2g of PVDF, mix them, and bake them in a forced-air drying oven at 90℃ for 8h.

[0129] (4) Disperse the mixture obtained from drying in (3) in 4.5 ml of NMP and stir thoroughly for 12 h to obtain a uniform slurry.

[0130] (5) Polish the zinc foil to remove the oxide layer, and then clean it with anhydrous ethanol. After the ethanol has completely evaporated, the pretreated zinc foil is obtained. Then place the pretreated zinc foil on a coating machine and coat it with the slurry from (4). The coating thickness is 10 μm.

[0131] (6) The zinc foil with coating obtained in (5) is placed in a muffle furnace and baked at 90°C for 12 hours to obtain the aqueous zinc-ion battery negative electrode protective coating based on coal gangue, that is, the zinc foil with metakaolin negative electrode protective coating.

[0132] The electrochemical performance of the aqueous zinc-ion battery anode protective coating based on coal gangue prepared in this embodiment was tested:

[0133] (1) A Zn / Zn symmetric cell was assembled using zinc foil with a metakaolin negative electrode protective coating prepared in Example 3 with a diameter of 1.3 cm as the electrode and glass fiber membrane with a diameter of 2 cm as the separator. The electrolyte was a 2M aqueous solution of ZnSO4.

[0134] (2) Use the Blue Battery Testing System to test the electrochemical performance.

[0135] Figure 15 The results of Example 3 show a bare zinc and a Zn / Zn symmetric cell with a metakaolin anode protective coating at 4.4 mA / cm². 2 The cycle time-voltage curve at current density shows that the coated symmetrical battery can cycle for 1000 hours, while the bare zinc symmetrical battery becomes unstable after only 450 hours and fails after 830 hours. This indicates that the metakaolin negative electrode protective coating can protect the zinc-ion battery and extend the service life of the symmetrical zinc-ion battery.

[0136] Example 4

[0137] This embodiment discloses a method for preparing a protective coating for the negative electrode of an aqueous zinc-ion battery based on coal gangue. The method specifically includes the following steps:

[0138] (1) Take 50g of coal gangue with a particle size of 3-5cm and place it in a GT-2 sealed sample preparation pulverizer. Grind for 7 minutes using steel balls as the grinding media. The specific amounts of steel balls used are: 4.4kg of 30mm steel balls, 5.74kg of 25mm steel balls, 3.04kg of 20mm steel balls, and 1.82kg of 15mm steel balls. After grinding, pass the coal gangue through a 200-mesh sieve to obtain finely ground coal gangue with a particle size of less than 75μm, which is then ready for use.

[0139] (2) Take 1g of finely ground coal gangue from (1) and place it in a VTL1500 vertical tube furnace for calcination. The simulated gas is formed by mixing two gases (N2 and O2) in a mixing box (VN2∶VO2=4∶1). The total gas flow rate is 600mL / min, the heating rate is 10℃ / min, the calcination temperature is 800℃, and the calcination time is 3h to obtain amorphous metakaolin.

[0140] (3) The amorphous metakaolin described in (2) is placed in a mortar and ground until the particle size is less than 75μm. Take 0.9g of the ground amorphous metakaolin and 0.1g of PVDF, mix them, and bake them in a forced-air drying oven at 90℃ for 8h.

[0141] (4) Disperse the mixture obtained from drying in (3) in 3 ml of NMP and stir thoroughly for 12 h to obtain a uniform slurry.

[0142] (5) Polish the zinc foil to remove the oxide layer, and then clean it with anhydrous ethanol. After the ethanol has completely evaporated, the pretreated zinc foil is obtained. Then place the pretreated zinc foil on a coating machine and coat it with the slurry from (4). The coating thickness is 20 μm.

[0143] (6) The zinc foil with coating obtained in (5) is placed in a muffle furnace and baked at 110°C for 12 hours to obtain the aqueous zinc-ion battery negative electrode protective coating based on coal gangue, i.e., the zinc foil with metakaolin negative electrode protective coating.

[0144] The electrochemical performance of the aqueous zinc-ion battery anode protective coating based on coal gangue prepared in this embodiment was tested:

[0145] (1) A Zn / Zn symmetric cell was assembled using zinc foil with a metakaolin negative electrode protective coating prepared in Example 4 with a diameter of 1.3 cm as the electrode and a glass fiber membrane with a diameter of 2 cm as the separator. The electrolyte was a 2M aqueous solution of ZnSO4.

[0146] (2) Use the Blue Battery Testing System to test the electrochemical performance.

[0147] Figure 16 The bare zinc and Zn / Zn symmetric cells with metakaolin anode protective coating shown in Example 4 are at 1 mA / cm². 2 The time-voltage curves after 900 hours of cycling at current density show that the overpotential of the coated symmetrical cell (average 43mV) is lower than that of the bare zinc electrode (average 56mV), indicating that the metakaolin anode protective coating does indeed reduce the overpotential of zinc ion deposition and accelerates the zinc ion deposition / stripping process.

[0148] Example 5

[0149] This embodiment discloses a method for preparing a protective coating for the negative electrode of an aqueous zinc-ion battery based on coal gangue. The method specifically includes the following steps:

[0150] (1) Take 50g of coal gangue with a particle size of 3-5cm and place it in a GT-2 sealed sample preparation pulverizer. Grind it for 10min using gravel as the grinding medium. After grinding, pass the coal gangue through a 200-mesh sieve to obtain finely ground coal gangue for later use.

[0151] (2) Take 1g of finely ground coal gangue from (1) and place it in a VTL1500 vertical tube furnace for calcination. The simulated gas is formed by mixing two gases (N2 and O2) in a mixing box (VN2∶VO2=4∶1). The total gas flow rate is 700mL / min, the heating rate is 10℃ / min, the calcination temperature is 900℃, and the calcination time is 4.5h to obtain amorphous metakaolin.

[0152] (3) The amorphous metakaolin described in (2) is placed in a mortar and ground until the particle size is less than 75 μm. Take 0.7 g of the ground amorphous metakaolin and 0.3 g of PVDF, mix them, and bake them in a forced-air drying oven at 100°C for 8 h.

[0153] (4) Disperse the mixture obtained from drying in (3) in 2 ml of NMP and stir thoroughly for 12 h to obtain a uniform slurry.

[0154] (5) Polish the zinc foil to remove the oxide layer, and then clean it with anhydrous ethanol. After the ethanol has completely evaporated, the pretreated zinc foil is obtained. Then place the pretreated zinc foil on a coating machine and coat it with the slurry from (4). The coating thickness is 10 μm.

[0155] (6) The zinc foil with coating obtained in (5) is placed in a muffle furnace and baked at 110°C for 12 hours to obtain the aqueous zinc-ion battery negative electrode protective coating based on coal gangue, i.e., the zinc foil with metakaolin negative electrode protective coating.

[0156] The electrochemical performance of the aqueous zinc-ion battery anode protective coating based on coal gangue prepared in this embodiment was tested:

[0157] (1) A Zn / Zn symmetric cell was assembled using zinc foil with a metakaolin negative electrode protective coating prepared in Example 5 with a diameter of 1.3 cm as the electrode and glass fiber membrane with a diameter of 2 cm as the separator. The electrolyte was a 2M aqueous solution of ZnSO4.

[0158] (2) Use the Blue Battery Testing System to test the electrochemical performance.

[0159] Figure 17 The results of Example 5 show a Zn / Zn symmetric cell with bare zinc and a metakaolin anode protective coating at 1.8 mA / cm². 2The time-voltage curves after 50 hours of cycling at current density show that the overpotential of the coated symmetrical cell (average 40mV) is lower than that of the bare zinc electrode (average 52mV), indicating that the metakaolin anode protective coating does indeed reduce the overpotential of zinc ion deposition and accelerates the zinc ion deposition / stripping process.

[0160] Example 6

[0161] This embodiment discloses a method for preparing a protective coating for the negative electrode of an aqueous zinc-ion battery based on coal gangue. The method specifically includes the following steps:

[0162] (1) Take 50g of coal gangue with a particle size of 3-5cm and place it in a GT-2 sealed sample preparation pulverizer. Grind it for 6 minutes using steel rods as the grinding media. After grinding, pass the coal gangue through a 200-mesh sieve to obtain finely ground coal gangue for later use.

[0163] (2) Take 1g of finely ground coal gangue from (1) and place it in a VTL1500 vertical tube furnace for calcination. The simulated gas is formed by mixing two gases (N2 and O2) in a mixing box (VN2∶VO2=4∶1). The total gas flow rate is 700mL / min, the heating rate is 10℃ / min, the calcination temperature is 1000℃, and the calcination time is 5h to obtain amorphous metakaolin.

[0164] (3) The amorphous metakaolin described in (2) is placed in a mortar and ground until the particle size is less than 75 μm. Take 0.6 g of the ground amorphous metakaolin and 0.4 g of PVDF, mix them, and bake them in a forced-air drying oven at 90°C for 8 h.

[0165] (4) Disperse the mixture obtained from drying in (3) in 4 ml of NMP and stir thoroughly for 12 h to obtain a uniform slurry.

[0166] (5) Polish the zinc foil to remove the oxide layer, and then clean it with anhydrous ethanol. After the ethanol has completely evaporated, the pretreated zinc foil is obtained. Then place the pretreated zinc foil on a coating machine and coat it with the slurry from (4). The coating thickness is 20 μm.

[0167] (6) The zinc foil with coating obtained in (5) is placed in a muffle furnace and baked at 80°C for 12 hours to obtain the aqueous zinc-ion battery negative electrode protective coating based on coal gangue, i.e., the zinc foil with metakaolin negative electrode protective coating.

[0168] The electrochemical performance of the aqueous zinc-ion battery anode protective coating based on coal gangue prepared in this embodiment was tested:

[0169] (1) Weigh 0.7g of MnO2 powder, 0.2g of conductive carbon black and 0.1g of PVDF. Mix them evenly in a 20mL glass bottle, add 4.5mL of NMP as solvent, and stir magnetically for 8h to obtain a uniform slurry.

[0170] (2) The slurry is slowly and evenly coated onto the smooth stainless steel foil surface using a coating machine, and then it is heated and baked at 90°C for 12 hours in a forced-air drying oven to completely remove the solvent, and used as the positive electrode sheet for zinc-ion batteries.

[0171] (3) Stainless steel foil with MnO2 positive electrode material and negative electrode with metakaolin protective coating were cut into disc-shaped electrodes with diameters of 1.3 cm and 1.5 cm, respectively. The effective loading of MnO2 on the positive electrode was 6 mg / cm³. 2 .

[0172] (4) A button-type zinc-ion battery was assembled using stainless steel foil with MnO2 as the positive electrode, zinc foil with metakaolin protective coating prepared in Example 6 as the negative electrode, and glass fiber membrane with a diameter of 2 cm as the separator. The electrolyte was an aqueous solution of 2M ZnSO4 and 0.1M MnSO4.

[0173] (5) Use the Blue Battery Testing System to test the electrochemical performance.

[0174] Figure 18 The diagram shows a comparison of the long-cycle performance of bare zinc and full cells with metakaolin anode protective coating in Example 6 under 5C operation. The results show that the full cell with coating has a capacity of 64.9 mAh / g and a capacity retention of 59% after 900 cycles, while the full cell with bare zinc stops working after 318 cycles and has a lower capacity than the full cell with coating. This indicates that the full cell with coating has better long-cycle performance and can cycle, which shows that the coating has a significant optimization effect on the zinc anode and can extend the long-cycle number of the full cell.

[0175] Example 7

[0176] This embodiment discloses a method for preparing a protective coating for the negative electrode of an aqueous zinc-ion battery based on coal gangue. The method specifically includes the following steps:

[0177] (1) Take 50g of coal gangue with a particle size of 3-5cm and place it in a GT-2 sealed sample preparation pulverizer. Grind for 10min. The grinding media is steel balls. The specific amounts of steel balls used are: 4.4kg of 30mm steel balls, 5.74kg of 25mm steel balls, 3.04kg of 20mm steel balls, and 1.82kg of 15mm steel balls. After grinding, pass the coal gangue through a 200-mesh sieve to obtain finely ground coal gangue with a particle size of less than 75μm, and set it aside for later use.

[0178] (2) Take 1g of finely ground coal gangue from (1) and place it in a VTL1500 vertical tube furnace for calcination. The simulated gas is formed by mixing two gases (N2 and O2) in a mixing box (VN2∶VO2=4∶1). The total gas flow rate is 800mL / min, the heating rate is 10℃ / min, the calcination temperature is 900℃, and the calcination time is 4h to obtain amorphous metakaolin.

[0179] (3) The amorphous metakaolin described in (2) is placed in a mortar and ground until the particle size is less than 75 μm. Take 0.9 g of the ground amorphous metakaolin and 0.1 g of PVDF, mix them, and bake them in a forced-air drying oven at 90°C for 8 h.

[0180] (4) Disperse the mixture obtained from drying in (3) in 3.5 ml of NMP and stir thoroughly for 12 h to obtain a uniform slurry.

[0181] (5) Polish the zinc foil to remove the oxide layer, and then clean it with anhydrous ethanol. After the ethanol has completely evaporated, the pretreated zinc foil is obtained. Then place the pretreated zinc foil on a coating machine and coat it with the slurry from (4). The coating thickness is 5 μm.

[0182] (6) The zinc foil with coating obtained in (5) is placed in a muffle furnace and baked at 90°C for 12 hours to obtain the aqueous zinc-ion battery negative electrode protective coating based on coal gangue, that is, the zinc foil with metakaolin negative electrode protective coating.

[0183] Comparative Example 1

[0184] The specific steps for testing the performance of zinc-ion batteries with or without a protective coating for the negative electrode of an aqueous zinc-ion battery based on coal gangue are as follows:

[0185] (1) Weigh 0.7g of MnO2 powder, 0.2g of conductive carbon black and 0.1g of PVDF. Mix them evenly in a 20mL glass bottle, add 4.5mL of NMP as solvent, and stir magnetically for 8h to obtain a uniform slurry.

[0186] (2) The slurry is slowly and evenly coated onto the smooth stainless steel foil surface using a coating machine, and then it is heated and baked at 90°C for 12 hours in a forced-air drying oven to completely remove the solvent, and used as the positive electrode sheet for zinc-ion batteries.

[0187] (3) Stainless steel foil and zinc foil with MnO2 positive electrode material, or zinc foil with metakaolin protective coating prepared in Example 1, were cut into disc-shaped electrodes with diameters of 1.3 cm and 1.5 cm, respectively. The effective loading of MnO2 on the positive electrode was 6 mg / cm³. 2 .

[0188] (4) A button-type zinc-ion battery was assembled using stainless steel foil with MnO2 as the positive electrode, zinc foil or zinc foil with metakaolin protective coating prepared in Example 1 as the negative electrode, and a glass fiber membrane with a diameter of 2 cm as the separator. The electrolyte was an aqueous solution of 2M ZnSO4 and 0.1M MnSO4.

[0189] (5) A Zn / Zn symmetrical cell was assembled using zinc foil with a diameter of 1.3 cm or zinc foil with a metakaolin negative electrode protective coating prepared in Example 1 as electrodes and glass fiber membrane with a diameter of 2 cm as separator. The electrolyte was a 2M aqueous solution of ZnSO4.

[0190] (6) Place the assembled Zn / Zn symmetrical battery from (5) onto the clamp connected to the test channel of the Blue Battery Test System for long-cycle testing, setting the current density to 0.4 mA / cm². 2 .

[0191] (7) Place the assembled full battery in (4) on the clamp connected to the test channel of the Blue Battery Test System for long-cycle testing, and set the cycle rate to 3C.

[0192] (8) Place the assembled full battery in (4) on the clamp connected to the test channel of the Blue Battery Test System for rate performance testing. Set the rate to 1C, 3C, 5C, 10C, and 20C, and cycle 5 times under each rate condition.

[0193] Figure 3 (a) shows that after 300 cycles, the large agglomerates on the bare zinc surface are zinc dendrites formed by the deposition of zinc ions over a long period of time. These zinc dendrites are disordered, have varying sizes, and are very easy to detach from the zinc anode surface, causing capacity loss in the battery. They can also puncture the glass fiber separator and contact the positive electrode, causing an internal short circuit in the battery. Figure 3 (b) After 300 cycles, the coating on the negative electrode was peeled off, exposing the bare zinc foil. SEM revealed that the zinc dendrites under the coating were very regular and had a specific growth morphology, with no isolated protrusions. The zinc dendrites were distributed in a lamellar pattern on the zinc foil surface, with most dendrites parallel to the zinc foil surface. In the presence of the coating, the zinc dendrites grew in a uniform manner, making it difficult to form large protrusions, effectively preventing gas evolution on the negative electrode surface and short circuits in the battery. This indicates that the coating effectively suppressed the occurrence of side reactions.

[0194] Figure 5 The results show that in Comparative Example 1, bare zinc and a Zn / Zn symmetric cell with a metakaolin anode protective coating are used at 0.4 mA / cm². 2The time-voltage curves after 1000 hours of cycling at current density show that the overpotential of the coated symmetrical cell (average 47mV) is lower than that of the bare zinc electrode (average 82mV), indicating that the metakaolin anode protective coating does indeed reduce the overpotential of zinc ion deposition and accelerates the zinc ion deposition / stripping process. Figure 6 The results show the long-term cycling performance of the bare zinc and the full cell with metakaolin anode protective coating in Comparative Example 1 under 3C operation. The results show that the capacity of the coated full cell after 400 cycles is 213.9 mAh / g with a capacity retention of 92.6%, while the capacity of the bare zinc full cell after 400 cycles is 138.1 mAh / g with a capacity retention of 66.7%. Moreover, the capacity of the coated full cell is higher than that of the bare zinc full cell throughout the entire cycle process, indicating that the coated full cell has better long-term cycling performance. The fact that it can cycle shows that the coating has a significant optimization effect on the zinc anode, which can extend the long-term cycling number of the full cell and improve the capacity retention of the cell.

[0195] Comparative Example 2: Obtaining a zinc-ion battery negative electrode protective coating by not using calcination to treat coal gangue.

[0196] (1) Take 50g of coal gangue with a particle size of 3-5cm and place it in a GT-2 sealed sample preparation pulverizer. Grind for 6 minutes using steel balls as the grinding media. The specific amounts of steel balls used are: 4.4kg of 30mm steel balls, 5.74kg of 25mm steel balls, 3.04kg of 20mm steel balls, and 1.82kg of 15mm steel balls. After grinding, pass the coal gangue through a 200-mesh sieve to obtain finely ground coal gangue with a particle size of less than 75μm, which is then ready for use.

[0197] (2) The finely ground coal gangue is placed in a mortar and ground until the particle size is less than 75μm. Take 0.9g of the ground coal gangue and 0.1g of PVDF, mix them, and bake them in a forced-air drying oven at 90℃ for 8h.

[0198] (3) Disperse the mixture obtained from drying in (2) in 4.5 ml of NMP and stir thoroughly for 12 h to obtain a uniform slurry.

[0199] (4) The zinc foil is polished to remove the oxide layer, and then cleaned with anhydrous ethanol. After the ethanol has completely evaporated, the pretreated zinc foil is obtained. Then the pretreated zinc foil is placed on a coating machine, and the slurry in (3) is placed on the zinc foil for coating. The coating thickness is 10 μm.

[0200] (5) The zinc foil with coating obtained in (5) is placed in a muffle furnace and baked at 90°C for 12 hours to obtain a zinc-ion battery negative electrode protective coating based on coal gangue without calcination treatment.

[0201] In this comparative example, the lack of calcination of the coal gangue affected the porosity and specific surface area of ​​the protective coating. This resulted in the inability to effectively suppress side reactions during battery operation, leading to severe hydrogen evolution and significant volume expansion of the battery. Figure 7 ).

[0202] Comparative Example 3: Zinc-ion battery negative electrode protective coatings were prepared using other calcination temperatures.

[0203] (1) Take 50g of coal gangue with a particle size of 3-5cm and place it in a GT-2 sealed sample preparation pulverizer. Grind for 6 minutes using steel balls as the grinding media. The specific amounts of steel balls used are: 4.4kg of 30mm steel balls, 5.74kg of 25mm steel balls, 3.04kg of 20mm steel balls, and 1.82kg of 15mm steel balls. After grinding, pass the coal gangue through a 200-mesh sieve to obtain finely ground coal gangue with a particle size of less than 75μm, which is then ready for use.

[0204] (2) Take 1g of the finely ground coal gangue described in (1) and place it in a VTL1500 vertical tube furnace for calcination. The simulated gas is formed by mixing two gases (N2 and O2) in a mixing box (VN2∶VO2=4∶1). The total gas flow rate is 500mL / min, the heating rate is 10℃ / min, the calcination temperature is 400℃, and the calcination time is 4h to obtain the calcined coal gangue.

[0205] (3) The calcined coal gangue described in (2) is placed in a mortar and ground until the particle size is less than 75 μm. 0.9 g of the ground coal gangue and 0.1 g of PVDF are mixed and placed in a forced-air drying oven at 90°C for 8 h.

[0206] (4) Disperse the mixture in (3) in 4.5 ml of NMP and stir thoroughly for 12 h to obtain a uniform slurry.

[0207] (5) Polish the zinc foil to remove the oxide layer, and then clean it with anhydrous ethanol. After the ethanol has completely evaporated, the pretreated zinc foil is obtained. Then place the pretreated zinc foil on a coating machine and coat it with the slurry from (4). The coating thickness is 10 μm.

[0208] (6) The zinc foil with coating obtained in (5) is placed in a muffle furnace and baked at 90°C for 12 hours to obtain a zinc-ion battery negative electrode protective coating.

[0209] In Comparative Example 3, coal gangue was calcined at a lower temperature. Due to the excessively low calcination temperature, the kaolin in the coal gangue did not undergo a dehydroxylation reaction, resulting in a product with low activity. This product could not function as a physical barrier or ion transporter, and therefore could not effectively regulate zinc ion migration, leading to dendrite growth. Figure 8However, the full cells prepared using this method exhibit lower rate performance compared to full cells with bare zinc. Under 1, 3, 5, 10, and 20C conditions, the discharge specific capacities of the full cells with bare zinc were 245.9, 226.6, 173.6, 127.5, and 92.8 mAh / g, respectively, while the discharge specific capacities of the coated full cells were only 185.0, 164.9, 148.3, 117.9, and 80.3 mAh / g. Figure 9 ).

[0210] Comparative Example 4: A protective coating for the negative electrode of a zinc-ion battery was prepared using a higher temperature.

[0211] (1) Take 50g of coal gangue with a particle size of 3-5cm and place it in a GT-2 sealed sample preparation pulverizer. Grind for 6 minutes using steel balls as the grinding media. The specific amounts of steel balls used are: 4.4kg of 30mm steel balls, 5.74kg of 25mm steel balls, 3.04kg of 20mm steel balls, and 1.82kg of 15mm steel balls. After grinding, pass the coal gangue through a 200-mesh sieve to obtain finely ground coal gangue with a particle size of less than 75μm, which is then ready for use.

[0212] (2) Take 1g of the finely ground coal gangue described in (1) and place it in a VTL1500 vertical tube furnace for calcination. The simulated gas is formed by mixing two gases (N2 and O2) in a mixing box (VN2∶VO2=4∶1). The total gas flow rate is 500mL / min, the heating rate is 10℃ / min, the calcination temperature is 1100℃, and the calcination time is 4h to obtain the calcined coal gangue.

[0213] (3) The calcined coal gangue described in (2) is placed in a mortar and ground until the particle size is less than 75 μm. 0.9 g of the ground coal gangue and 0.1 g of PVDF are mixed and placed in a forced-air drying oven at 90°C for 8 h.

[0214] (4) Disperse the mixture obtained from drying in (3) in 4.5 ml of NMP and stir thoroughly for 12 h to obtain a uniform slurry.

[0215] (5) Polish the zinc foil to remove the oxide layer, and then clean it with anhydrous ethanol. After the ethanol has completely evaporated, the pretreated zinc foil is obtained. Then place the pretreated zinc foil on a coating machine and coat it with the slurry mentioned in (4). The coating thickness is 10 μm.

[0216] (6) The zinc foil with coating obtained in (5) is placed in a muffle furnace and baked at 90°C for 12 hours to obtain a zinc-ion battery negative electrode protective coating.

[0217] In Comparative Example 4, coal gangue was calcined at a higher temperature. Due to the excessively high temperature, the kaolin in the coal gangue underwent a recrystallization reaction, and the resulting product was partially mullite. This led to a lower overall porosity and activity in the coating, hindering the transport of zinc ions and causing dendrite growth. Figure 10 The full cell prepared using coal gangue calcined at 1100℃ exhibits lower long-cycle performance compared to a symmetric cell containing bare zinc. From Figure 11 It can be seen from this that at 0.5 mA / cm 2 Under current density cycling, the voltage-time fluctuations of the coated symmetrical cell were unstable, and a short circuit occurred after only 230 hours. At 0.5 mA / cm², the voltage remained stable. 2 After 650 hours, the overpotential of bare zinc remained at 68 mV. The coated symmetric cell exhibited a higher exchange current density and overpotential value (97 mV).

[0218] Comparative Example 5: Zinc-ion battery negative electrode protective coatings were prepared using different temperatures.

[0219] (1) Take 50g of coal gangue with a particle size of 3-5cm and place it in a GT-2 sealed sample preparation pulverizer. Grind for 6 minutes using steel balls as the grinding media. The specific amounts of steel balls used are: 4.4kg of 30mm steel balls, 5.74kg of 25mm steel balls, 3.04kg of 20mm steel balls, and 1.82kg of 15mm steel balls. After grinding, pass the coal gangue through a 200-mesh sieve to obtain finely ground coal gangue with a particle size of less than 75μm, which is then ready for use.

[0220] (2) Take 1g of the finely ground coal gangue described in (1) and place it in a VTL1500 vertical tubular furnace for calcination. The simulated gas is formed by mixing two gases (N2 and O2) in a mixing box (VN2∶VO2=4∶1). The total gas flow rate is 500mL / min, the heating rate is 10℃ / min, the calcination temperature is 500, 600, 700, 800, 900 and 1100℃ respectively, and the calcination time is 4h to obtain the calcined coal gangue.

[0221] (3) The calcined coal gangue described in (2) is placed in a mortar and ground until the particle size is less than 75 μm. 0.9 g of the ground coal gangue and 0.1 g of PVDF are mixed and placed in a forced-air drying oven at 90°C for 8 h.

[0222] (4) Disperse the mixture obtained from drying in (3) in 4.5 ml of NMP and stir thoroughly for 12 h to obtain a uniform slurry.

[0223] (5) Place the polished zinc foil on a coating machine and coat the slurry from (4) onto the zinc foil. The coating thickness is 10 μm, and a zinc foil with a calcined kaolin protective coating is obtained.

[0224] The zinc foil obtained in (5) was dried in a muffle furnace at 90°C for 12 hours.

[0225] Figure 12 The contact angle of the calcined coal gangue coating was tested at 500℃, 600℃, 700℃, 800℃, 900℃, and 1100℃. The figure shows that the contact angle is smallest at 800℃, at 34°. This is because when the coal gangue is calcined at 800℃, the kaolinite in the coal gangue transforms into metakaolinite. This process completely amorphizes the kaolinite into metakaolinite and decarbonizes the coal gangue, while preventing further crystallization of the metakaolinite into mullite at excessively high temperatures. Metakaolinite has the most active groups and the highest hydrophilicity.

[0226] Figure 13 Figures (a)-(f) show the surface morphology of the zinc anode after calcination of coal gangue coating at 500℃, 600℃, 700℃, 800℃, 900℃, and 1100℃, respectively, following 300 cycles. As can be seen from the figures, when the calcination temperature is 800℃, the surface microstructure of the negative electrode does not change significantly after 300 cycles.

[0227] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some changes or modifications to the above-described technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for preparing a protective coating for the negative electrode of an aqueous zinc-ion battery based on coal gangue, characterized in that: The method specifically includes the following steps: 1) Grind the coal gangue raw material and sieve it to obtain finely ground coal gangue; 2) The finely ground coal gangue described in step 1) is calcined to obtain amorphous metakaolin. 3) Grind the amorphous metakaolin described in step 2), then mix it with the binder according to the ratio and dry it. Then disperse the dried mixture in an organic solvent, mix it evenly, and obtain a uniform slurry. 4) The slurry described in step 3) is coated onto the pretreated zinc foil surface and dried to obtain the aqueous zinc-ion battery negative electrode protective coating based on coal gangue.

2. The method according to claim 1, characterized in that: Step (1) The grinding equipment used in the grinding is a GT-2 sealed sample preparation pulverizer.

3. The method according to claim 1, characterized in that: In step (1), the grinding time is 1-10 min; the particle size of the finely ground coal gangue is 20-100 μm.

4. The method according to claim 1, characterized in that: In step (2), the calcination is carried out using a mixed gas, preferably a mixed gas composed of N2 and O2; the total gas flow rate of the mixed gas is 200-700 mL / min.

5. The method according to claim 1, characterized in that: In step 2), the calcination temperature is 500-1000℃ and the calcination time is 2-5h.

6. The aqueous zinc-ion battery anode protective coating based on coal gangue prepared by the method according to any one of claims 1-5.

7. The application of the coal gangue-based aqueous zinc-ion battery anode protective coating prepared by the method of any one of claims 1-5 in the anode of an aqueous zinc-ion battery.

8. A negative electrode for an aqueous zinc-ion battery, characterized in that: The protective coating for the negative electrode of an aqueous zinc-ion battery based on coal gangue, prepared by the method described in any one of claims 1-5.

9. An aqueous zinc-ion battery, comprising a positive electrode, a negative electrode, a separator between the positive and negative electrodes, and an electrolyte, characterized in that: The negative electrode is the negative electrode of the aqueous zinc-ion battery according to claim 8.

10. A method for detecting the electrochemical performance of the protective coating on the negative electrode of an aqueous zinc-ion battery based on coal gangue prepared by the method of any one of claims 1-5, characterized in that: The method includes the following steps: 1) Preparation of Zn / MnO2 full cells using MnO2 as the positive electrode material of rechargeable zinc-ion batteries: MnO2 powder, conductive carbon black and binder were weighed in sequence according to the formula, mixed and then an organic solvent was added to disperse evenly to obtain a uniform slurry. 2) The slurry described in 1) is slowly and evenly coated onto a smooth stainless steel foil surface using a coating machine, and then heated and dried to be used as the positive electrode sheet for zinc-ion batteries. 3) Cut stainless steel foil with MnO2 positive electrode material and zinc foil negative electrode with metakaolin protective coating prepared by any one of claims 1-5 into disc-shaped electrodes; 4) A button-type zinc-ion battery is assembled using stainless steel foil with MnO2 as the positive electrode, zinc foil with metakaolin negative electrode protective coating prepared by any one of claims 1-5 as the negative electrode, and glass fiber membrane as the separator, and the electrolyte is an aqueous solution of ZnSO4 and MnSO4. 5) Using zinc foil with a metakaolin negative electrode protective coating prepared by the method described in any one of claims 1-5 as the electrode, and glass fiber membrane as the separator, a Zn / Zn symmetric cell is assembled, and the electrolyte is an aqueous solution of ZnSO4. 6) Test the battery performance on the assembled battery workstation and electrochemical testing system.